(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
Road Traffic Accident (RTA) is any vehicular accident occurring on the roadway i.e. originating on, terminating on, or involving a vehicle partially on the roadway. Road traffic accident ranks among the top causes of death in the world; after ischemic heart disease, it is projected to become the second leading cause in 2024. In developing countries, around 85 percent of all deaths caused by road accidents occur, and nearly half of these accidents happen in the Asia-Pacific region. India is responsible for around 10 percent of all road accident deaths in the whole world. Road traffic accidents in India is emerging as a major cause of death and injury with subsequent disability and burden on economy of a nation. The cost of burden due to RTA is estimated to be around 1-2% of a country’s gross national product (GNP) specifically in lower-income countries. In this study we have analyzed the 109 cases of road traffic accidents brought for examination by the police to the Department of Forensic Medicine & Toxicology, JGMCH, Jalpaiguri, West Bengal from the January 2024 to June 2024. All data were analysed by appropriate statistical tool (SPSS) software. In this study we found that the peak incidence of RTA was observed in the age group 21-40 years comprising 41.28% of the cases. Males (88.07%) outnumbered females (11.93%) and most of the accidents occurred between night times from 8pm to 6am. In 47.78% cases there was immediate death and cases are seen mainly in two wheeler occupants (42.20%). In two wheelers accidents, drivers (84.78%) were more commonly affected and in four wheelers accidents, front seaters were affected (55.55%). It has been observed the lungs injuries are common 32.11% cases compared to heart injuries 18.34% cases in thoracic involvement and liver with 14.67 % cases is more commonly affected abdominal organ compared to spleen (2.75%) in abdominal injuries.